THE EFFECT OF PROBLEM-BASED LEARNING (PBL) MODEL ON THE PROBLEM-SOLVING SKILLS IN SOCIAL SCIENCE IN ELEMENTARY SCHOOL - Sinta Maria Dewi; Haerudin; Siti Hasanah; Danial Kusumah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aims to determine the effect of the Problem-Based Learning (PBL) model on the social science problem-solving abilities of elementary school students. The research employed a Pre-Experimental Design using a One-Group Pretest–Posttest design. The findings show that the average post-test score was higher than the average pretest score, indicating an improvement in students’ problem-solving abilities after the implementation of the PBL model. The average pretest score was 58.10, while the average post-test score increased to 75.40. Hypothesis testing using a paired sample t-test at a significance level of 0.05 yielded a significance value of 0.000. Since 0.000 < 0.05, H₀ was rejected. These results demonstrate that the Problem-Based Learning (PBL) model has a significant effect on improving elementary school students’ social science problem-solving abilities.